A cultural side effect: mirror suppression in object recognition is triggered by letter knowledge in preschoolers. - Fernandes, Tânia (2016)
Since when, during reading development, does literacy impact object recognition and orientation processing? Is this impact specific to mirror images (e.g., d − b) or also apparent for other transformations (e.g., plane−rotations: d − p)? To answer these questions, forty−six 5−7−year−old preliterate preschoolers and first graders performed two same−different matching tasks tapping explicit (orientation−based) vs. automatic (shape−based) orientation processing of geometric shapes. On orientation−based judgments, first graders outperformed preschoolers. Preschoolers had the strongest difficulty in discriminating mirrored pairs. On shape−based judgments, first graders were slower for mirrored than identical pairs, and even slower than preschoolers. This mirror cost, a side−effect of learning to read, was allied with letter knowledge in preschoolers. Thus, mirror suppression emerges even before formal literacy instruction and generalizes to non−linguistic material.